PERSAHABATAN: MAKNA DAN KONTRIBUSINYA BAGI KEBAHAGIAAN DAN KESEHATAN LANSIA - Lestari, Made Diah (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2017)
Abstract — Activity theory has given an enormous perspective on ageing with the concept of successful ageing. The theory views older people as an active, productive, and sociable group. Social contact or participation is one of the indicators of an ageing-friendly community which has been declared by World Health Organization. Maintaining friendship is an example of social contact in older people. The pattern of friendship changes according to the abilities and needs in every stages of human development. The aim of the study is to find the pattern of friendship, the meaning of friendship, and friendship impact on physical and psychological healthiness in older people. The participants were 14 older people from 64 to 70 years old. The present study is a qualitative research using photovoice method. According to participatory and coding analysis, the study has found several themes which contributed to the pattern of friendship, namely the definition of who friends are and the duration of companionship. For the participants, friend is appreciated as someone who become part of their memory, someone who always serve openness, and someone who gets them away from loneliness. Friendship was seen as a type of relationship which is built by pure interest. Friendship activities that benefit the older people are getting together with friends, sharing experiences, finding solutions to the problems encountered, visiting friends, attending important events of friends, running hobby, and doing physical activity. The critical findings of the present study can be used for planning the management model of healthcare for the older people.  Abstrak— Activity theory telah memberikan perspektif yang baru dalam bidang gerontologi dengan konsep successful ageing. Teori ini menilai lanjut usia (lansia) sebagai kelompok yang aktif, produktif, dan masih mampu berkiprah dalam situasi sosial. Partisipasi sosial adalah salah satu indikator dari komunitas ramah lansia yang dideklarasikan oleh World Health Organization. Mampu menjaga persahabatan adalah salah satu dari bentuk kontak sosial dan partisipasi sosial bagi lansia. Pola-pola persahabatan berubah seiring dengan perkembangan usia seseorang. Tujuan dari penelitian ini adalah untuk melihat pola persahabatan, makna persahabatan, dan dampak persahabatan bagi kondisi fisik dan psikologis lansia. Responden penelitian ini adalah 14 orang lansia yang berusia 64 hingga 70 tahun dan aktif mengikuti kegiatan bersama teman. Penelitian ini menggunakan metode kualitatif dengan photovoice. Melalui analisis partisipatori dan koding, studi mendapatkan tema-tema yang berkontribusi pada pola persahabatan lansia, seperti siapa yang dianggap sebagai teman, durasi persahabatan dan pertemanan. Bagi responden, teman adalah sosok yang merupakan bagian dari memori masa lalu, seseorang yang menghadirkan keterbukaan, dan mampu menjauhkan mereka dari rasa kesepian. Persahabatan dinilai sebagai bentuk hubungan yang dibangun dari intensi yang murni tanpa tendensi apa pun. Aktivitas bersama sahabat yang mampu memberikan dampak positif bagi responden adalah berbagai pengalaman, mengunjungi teman, menghadiri acara-acara penting sahabat, menjalankan hobby bersama, dan berolahraga. Hasil dari penelitian ini mampu menjadi dasar bagi penatalaksanaan kesehatan bagi lansia.